Personal Recovery in the General Population: Comparison of Psychometric Properties of the Brief INSPIRE-O in Those With and Without Common Mental Disorders - Ruan, Xingjian; Vergeer-Hagoort, Femke; ten Have, Margreet; Luik, Annemarie I.; Tuithof, Marlous; Bohlmeijer, Ernst; ten Klooster, Peter M. (Assessment (Odessa, Fla.), 2025)
The 5-item Brief INSPIRE-O instrument, based on the Connectedness, Hope, Identity, Meaning in Life, and Empowerment framework, is a novel tool to assess personal recovery. Although initially developed for clinical populations, its conceptual alignment with core dimensions of psychological well-being suggests its potential applicability to a broader audience. The current study aimed to examine its validity, reliability, and measurement invariance across people with and without common mental disorders (CMDs). The scale was administered in a Dutch general population sample ( n = 5,451). Confirmatory factor analyses supported a unidimensional structure with robust factor loadings and scalar invariance across individuals with and without CMDs in the past year. In addition, the Brief INPSIRE-O showed acceptable reliability (ω = .71–.78) and the expected pattern of correlations with other health indicators supported its construct validity. In conclusion, the Brief INSPIRE-O appears to be a psychometrically sound measure of positive psychological functioning that can be validly used and compared across people with and without CMDs.